On-line social interactions and executive functions - Ybarra, Oscar; Winkielman, Piotr (Frontiers in Human Neuroscience, 2012)
A successful social interaction requires fast, on-line, and active construction of an ever-changing mental-model of another’s person beliefs, expectations, emotions, and desires. It also requires the ability to inhibit inappropriate behaviors, problem-solve, take-turns, and pursue goals in a distraction-rich environment. All these tasks rely on executive functions (EF)—working memory, attention/cognitive control, and inhibition. Executive functioning has long been viewed as relatively static. However, starting with recent reports of successful cognitive interventions, this view is changing and now EFs are seen as much more open to both short and long term “training,” “warm-up,” and “exhaustion” effects. Some of the most intriguing evidence comes from research showing how social interaction enhances performance on standard EF tests. Interestingly, the latest research indicates these EF benefits are selectively conferred by certain on-line, dynamic social interactions, which require participants to engage with another person and actively construct the model of their mind. We review this literature and highlight its connection with evolutionary and cultural theories emphasizing links between intelligence and social life.